Penilaian Proses dan Hasil Belajar PAI Kurikulum Merdeka Berbasis Taksonomi Bloom Revisi (2024) - Humaira; Ansor (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
This study aims to examine the assessment of learning processes and outcomes in Islamic Religious Education (PAI) within the Merdeka Curriculum based on the Revised Bloom’s Taxonomy. This research employs a qualitative approach with a library research method by analyzing various relevant scientific literatures, including books, journal articles, and official documents. The findings indicate that assessment in the Merdeka Curriculum has shifted from outcome-based assessment to a more process-oriented, continuous, and authentic assessment. The integration of the Revised Bloom’s Taxonomy provides a systematic framework for developing assessment instruments that cover both lower-order and higher-order thinking skills (HOTS). However, its implementation still faces several challenges, such as limited teacher understanding, the dominance of low-level cognitive assessments, and the suboptimal evaluation of affective and psychomotor domains. Therefore, strategic efforts are needed, including improving teacher competence, developing innovative assessment instruments, and utilizing technology in the evaluation process. This study contributes to the development of a more comprehensive, authentic, and relevant conceptual model of PAI assessment in line with the demands of 21st-century education.